Az egyetemi infrastruktúra kiépülése a Ferencz József Tudományegyetem Szegedre kerülését követően - Kiss, Róbert (Per Aspera ad Astra, 2014)
Due to the war situation in Transylvania in 1919, the Ferencz József University was forced to flee the city of Kolozsvár. After a short stay in Buda, the Ministry of Religion and Education and the political leaders of Szeged negotiated its relocation to Szeged. In the five-year period following the university’s opening in October 1921, it experienced hardships and everyday operational problems, but from 1926 it received significant state resources thanks to the Minister of Religion and Education, Kuno Klebersberg. Although the Great Depression resulted in the depletion of these resources, as a result of the prior constructions and investments, the university could find its final home in Szeged, and could become a modern think tank of Western European standards. (Translated by Ágnes Lengvári) Fotó: Fortepan / Somlai Tibor